Systemic Interaction of Center and Regions in Ukraine (basics of national-civilizational security) - Stolyarov, V.; Shinkaryuk, O.; Stolyarova, V. (Економічний вісник Донбасу, 2020)
The article poses and solves the problem of achieving coordinated interaction between the Center and the Regions as a single, organic and dynamic system of a sovereign independent state. Modern approaches of liberal and planned principles of overcoming bureaucratic and corrupt arbitrariness and urgent resuscitation with intensive revival of economic and vital activity of Ukraine, which is purposefully destroyed under external influence, are considered. The main provisions of the report of the President of France Emmanuel Macron in August 2019 on the Great Fracture in European and world civilization processes are revealed. The main ideas and directions of the Plan of the Great Reset and implementation of the fourth industrial revolution of June 2020 of the Davos World Economic Forum are presented. A meaningful chronology of the formation of the organizational mechanism for the introduction of inclusive capitalism and its management and staffing is given. The equivalence of the principles of homeostasis of economic and biological systems is considered by comparing the restoration of the viability of the global network economy and marine biological systems (on the example of a vampire octopus). Generalized signs of international and state terrorism in Ukraine. The necessity to change the Anglo-Saxon model of open market economy to socially oriented one using the doctrine of 3 "S": social forecasting, social planning and social management is substantiated. It is proposed to use the experience of the United States and Great Britain on social planning and the European financial model of people's capitalism. Based on the proposals of Emelyanov O.S. to enhance the role of the Center in cooperation with the Regions, it is recommended to develop National and Regional Human Development Programs. It is proposed to develop a Planning Code of Ukraine based on the provisions of the model of socially adequate management with encyclopedic criteria for their use at the national and regional levels of government. У статті поставлена і вирішена проблема досягнення узгодженої взаємодії Центру і Регіонів як єдиної, органічної і динамічної системи суверенної самостійної держави. Розглянуті сучасні підходи ліберальних і планових принципів виходу з чиновницько-корупційного свавілля та термінова реанімація з інтенсивним відродженням господарської та життєвої діяльності України, яка цілеспрямовано руйнується під зовнішнім впливом. Розкрито основні положення доповіді Президента Франції Еммануеля Макрона в серпні 2019 року щодо Великого перелому у Європейських і світових цивілізаційних процесах. Представлено основні ідеї і напрями Плану Великого Перезавантаження та здійснення четвертої промислової революції червня 2020 року Давоського Всесвітнього Економічного Форуму. Наведена змістовна хронологія формування організаційного механізму впровадження інклюзивного капіталізму, його керівного і кадрового забезпечення. Розглянуто рівнозначність принципів гомеостазу економічних і біологічних систем шляхом зіставлення відновлення живучості світової мережевої економіки і морських біологічних систем (на прикладі спрута-вампіра). Узагальнено ознаки міжнародного та державного тероризму в Україні. Обґрунтовано необхідність зміни англосаксонської моделі ринкової економіки відкритого типу на соціально-орієнтовану з використанням доктрини трьох "С": соціальне прогнозування, соціальне планування і соціальне управління. Запропоновано використати досвіду США і Великобританії стосовно соціального планування і європейської фінансової моделі народного капіталізму. На основі пропозицій О. С. Ємельянова щодо підвищення ролі Центру у взаємодії з Регіонами рекомендується розробляти Національну і Регіональні програми людського розвитку. Пропонується розробити Плановий кодекс України на положеннях моделі соціально-адекватного менеджменту з енциклопедичними критеріями їх використання на національному та регіональних рівнях державного управління. В статье поставлена и решена проблема достижения согласованного взаимодействия Центра и Регионов как единой, органической и динамической системы суверенного самостоятельного государства. Рассмотрены современные подходы либеральных и плановых принципов выхода из чиновничье-коррупционного произвола и срочная реанимация с интенсивным возрождением хозяйственной деятельности и человеческой жизни в Украине, которая целенаправленно разрушается под внешним воздействием. Раскрыты основные положения доклада Президента Франции Эммануэля Макрона в августе 2019 года о Большом переломе в Европейских и мировых цивилизационных процессах. Представлены основные идеи и направления Плана Великой Перезагрузки и осуществления четвертой промышленной революции Давосского Всемирного Экономического Форума (июнь, 2020). Приведена содержательная хронология формирования организационного механизма внедрения инклюзивного капитализма и его руководящего и кадрового обеспечения. Рассмотрена равнозначность принципов гомеостаза экономических и биологических систем путем сопоставления восстановления живучести мировой сетевой экономики и морских биологических систем (на примере спрута-вампира). Обобщены признаки международного и государственного терроризма в Украине. Обоснована необходимость изменения англосаксонской модели рыночной экономики открытого типа на социально-ориентированную с использованием доктрины трех "С": социальное прогнозирование, социальное планирование и социальное управление. Предложено использовать опыт США и Великобритании в отношении социального планирования и европейской финансовой модели народного капитализма. На основе предложений О. С. Емельянова по повышению роли Центра во взаимодействии с Регионами рекомендуется разрабатывать Национальную и Региональные программы человеческого развития. Предлагается разработать Плановый кодекс Украины на положениях модели социально-адекватного менеджмента с энциклопедическими критериями их использования на национальном и региональных уровнях государственного управления.